Corporate Social Responsibility in Work-Based Learning: Industry Perspective - Ismail, Syamhanim; Mohamad, Mimi Mohaffyza; Muriati, Dewi Eka; Rahmawati, Yuni (Online Journal for TVET Practitioners, 2023)
Work-Based Learning is one of the learnings requiring collaboration between educational institutions and industry. Without collaboration, the educational institution cannot place their student for training, and the industry cannot fulfill its Corporate Social Responsibility (CSR). The collaboration will bring a win-win situation for each party. To be established in Malaysia, each industry must carry out Corporate Social Responsibility (CSR) and can enjoy tax exemption. This study explores the industrial experience in CSR while collaborating on Advanced Diploma and bachelor’s degree with an Honors program using WBL methods. This study was conducted using multiple case studies of qualitative approach with semi-structured interviews and guided by two sets of the protocol. This study involved eight participants from Polytechnic UA, Polytechnic SA, company A, company B, and company C. The finding shows that companies A and B agreed that their collaboration in the WBL program could fulfill the CSR and enjoy the tax exemption. It has contrasted with company C. Company C only fulfilled its CSR for three years and stopped due to financial problems. However, Company C still collaborates with Polytechnic SA in WBL program. Based on this finding, more industries will be interested in fulfilling their CSR by collaborating with educational institutions using WBL methods.